Stachyonic Acid: A Dengue Virus Inhibitor from Basilicum polystachyon. Issue 22 (29th March 2019) - Tan, Yuen P.; Houston, Sevan D.; Modhiran, Naphak; Savchenko, Andrei I.; Boyle, Glen M.; Young, Paul R.; Watterson, Daniel; Williams, Craig M.
Abstract: Stachyonic acid A, arising from the first in‐depth phytochemical investigation of the herb Basilicum polystachyon, was found to display potent inhibitory activity against dengue virus, with limited cytotoxicity. Andrographolide, a known dengue virus inhibitor and closely related labdane‐type diterpene, is structurally more complex but displayed poor antiviral activity in the PRNT assay, and increased cytotoxicity in comparison. Furthermore, a Diels–Alder reaction with PTAD identified the active pharmacophore of stachyonic acid to be the conjugated diene. Abstract : Stachyonic acid A, isolated from the herb Basilicum polystachyon, was found to display potent inhibitory activity against dengue virus, and out‐perform the structurally more complex, albeit related labdane, andrographolide. In addition, the active pharmacophore was identified as the conjugated diene opening up a new avenue for anti‐DENV discovery.